PENGEMBANGAN HANDOUT BERGAMBAR YANG DIAWALI PETA KONSEP PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN UNTUK SMP/ MTsN - Sulassri, Milda; Risdawati, M.Si., Renny; Susanti, Diana (Pendidikan Biologi, 2014)
ABSTRACT Handout is learning materials given to the students when they are involved in a learning activity. Teachers can design handout by referring to several literatures which are relevant to the basic competence to be achieved. Based on the previous observation and interview condukted at MTsN Lubuk Buaya Padang, it was found that the handout for teaching Biology in the second semester  in  class  VIII  was  not  available  yet.  They  used  Student  Worksheet  designed  by commercial publisher and textbook provided at school. The availabel textbooks were limited and they is contain black and white pictures. Whereas,  in the learning process, the studens were required to understand the concepts of the learning materials being presented. To understand the concepts, the students needed to be led by adding conceptual map in the beginning of the learning materials.  They were  intended  to  describe  meaningful relationship  among  the concepts.  This research was intended to produce a pictured handout started with conceptual map on Stucture and Function of Plant Tissues which was valid and practical. This was a developmental research which used 4-D models including defining, designing, developing, and disseminating. The data collected was primary data gotten from the lecturers, the teachers and the students. The data gotten was analyzed descriptively. The result of the research revealed that the handout developed was valid in which the validity score was 87,80%, the handout was also practic. This could be seen from the score given by the teachers which was 81,94% and the score given by the students which was88,27%. Thus, it was concluded that the handout developed had been very valid and very practic.